THE LEVEL OF EMPOWERMENT OF RICE FARMERS IN PEGAYUT VILLAGE OGAN ILIR KABUPATEN DISTRICT - Sri Utami; Mega Nurrizalia (IKIP Siliwangi Bandung, 2023)
This study aims to determine the level of empowerment of rice farmers in Pegayut village, Ogan Ilir Regency. This type of research is descriptive research with a quantitative approach. Data collection techniques were carried out using questionnaires and documentation. The population in this study, namely rice farmers in Pegayut village as many as 162 people, using the calculation with the Slovin formula and obtained a sample of 62 respondents. Validity test with a significant level of 5%. The reliability test using the Cronbach Alpha formula obtained a value of 0.893 with very high reliability criteria. The results showed that the level of empowerment of rice farmers in Pegayut village was 76% with high category. This can be seen from the indicators of empowerment, namely 1) the fulfillment of basic needs of farmers by 76.55% in the high category, 2) the ability of farmers to manage agricultural information by 72.92% in the high category, 3) the ability of farmers to make decisions by 81 .15% in the high category, is said to be high because farmers are able to meet their daily needs in terms of clothing, food and shelter and the educational needs of children, farmers are able to manage agricultural information very well and are able to make good decisions. Then, 4) the ability of farmers to market their products is 61.15% with sufficient category, and 5) the ability of farmers to apply agricultural technology is 69.64% with sufficient category, this is because most farmers store their agricultural products and sell them if there are buyers and some farmers still grow rice using the traditional way. As for suggestions for rice farmers to further improve their ability to market their products and build cooperation between communities in order to create farmer groups.Keywords: Empowerment Level, Rice Farmers